Results of the Latarjet procedure for recurrent anterior dislocation of the shoulder in patients with epilepsy - Raiss, Patric (Journal of bone and joint surgery. B, British volume, 2012)
A total of 12 epileptic patients (14 shoulders) with recurrent seizures and anterior dislocations of the shoulder underwent a Latarjet procedure and were reviewed at a mean of 8.3 years (1 to 20) post-operatively. Mean forward flexion decreased from 165° (100° to 180°) to 160° (90° to 180°) (p = 0.5) and mean external rotation from 54° (10° to 90°) to 43° (5° to 75°) (p = 0.058). The mean Rowe score was 76 (35 to 100) at the final follow-up. Radiologically, all shoulders showed a glenoid-rim defect and Hill-Sachs lesions pre-operatively. Osteo-arthritic changes of the glenohumeral joint were observed in five shoulders (36%) pre-operatively and in eight shoulders (57%) post-operatively. Re-dislocation during a seizure occurred in six shoulders (43%). Five of these patients underwent revision surgery using a bone buttress from the iliac crest and two of these patients re-dislocated due to a new seizure. Due to the unacceptably high rate of re-dislocation after surgery in these patients, the most important means of reducing the incidence of further dislocation is the medical management of the seizures. The Latarjet procedure should be reserved for the well-controlled patient with epilepsy who has recurrent anterior dislocation of the shoulder during activities of daily living.